Adorno e i Minima Moralia. Una rilettura filosofico-pedagogica - Francesco Simoncini (Firenze University Press, 2018)
In Minima moralia, Theodor W. Adorno develops a discourse that bridges philosophy, sociology and pedagogy. The present article aims to highlight, in Adorno's work, the coexistence and the intertwining of these three dimensions, summing them up under the category of "form" - be it a social institution or a sign of the "formation" of every man. Other problems are then taken into account, namely the reification of forms and the decline of experience; finally, still following Minima moralia, the possibility of dismissing the very concepts of "form" and "formation" is discussed and rejected.